Comparison between Secondary Electron Microscopy Dopant Contrast Image (SEMDCI) and Electron Beam Induced Current (EBIC) for Laser Doping of Crystalline Silicon - Xu, Lujia; Hameiri, Ziv; Weber, Klaus; Yang, Xinbo (Energy procedia, 2014)
Laser doping of crystalline silicon has been the subject of intense research over the past decade, due to its potential to enable the fabrication of high efficiency and low-cost crystalline silicon solar cells. Information regarding the doping profile created by the process is critical for process optimisation, however is generally difficult to obtain. In this paper, a relatively new technique for characterising laser doping cross-sections — Secondary Electron Microscopy Dopant Contrast Image (SEMDCI) — is compared with the widely used Electron Beam Induced Current (EBIC) method. A good agreement between the two techniques regarding the p-n junction profile is demonstrated. The differences between the methods are attributed to the difference of the sensitivity. The comparison demonstrates the reliability and usefulness of the SEMDCI as a characterisation method for laser doping, which shows both the p-n junction outline and dopant distribution within the doped regions. The differences between the methods and the challenges associated with the application of the SEMDCI method are also discussed.